ANESTHESIA OF CATS AND DOGS - Djabbarova Dilnoza; Abidov Ahmadjon; Sayfullayeva Makhbuba (Journal of new century innovations, 2023)
Annotation. In this article, a series of information about anesthetic drugs, premedications and their application techniques, used to perform surgery on pets, cats and dogs, which are an integral part of human life today, is covered.